2019
DOI: 10.1177/2309499019893515
|View full text |Cite
|
Sign up to set email alerts
|

Similar outcomes between ultracongruent and posterior-stabilized insert in total knee arthroplasty: A propensity score-matched analysis

Abstract: Purpose: (1) To compare postoperative range of motion (ROM), stability, and clinical outcomes between fixed-bearing posterior-stabilized (PS) and ultracongruent (UC). (2) The effect of postoperative stability on ROM and clinical outcomes was also evaluated in both designs. Materials and methods: Propensity score matching was conducted for age, gender, body mass index, preoperative ROM, Western Ontario and McMaster Universities Osteoarthritis (WOMAC) index, Knee Society (KS) scores, hip–knee–ankle (HKA) alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Despite the different patterns of posterior tibial translation, the clinical outcomes observed in this study when using UC or PS designs are similar, and this is consistent with previous findings of some other studies with mobile‐bearing [14, 15, 19] or fixed‐bearing TKA [1, 13, 16, 23]. This study has also found similar functional outcomes between UC and PS designs, as it has been previously described in some studies [4, 21].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the different patterns of posterior tibial translation, the clinical outcomes observed in this study when using UC or PS designs are similar, and this is consistent with previous findings of some other studies with mobile‐bearing [14, 15, 19] or fixed‐bearing TKA [1, 13, 16, 23]. This study has also found similar functional outcomes between UC and PS designs, as it has been previously described in some studies [4, 21].…”
Section: Discussionsupporting
confidence: 92%
“…In this category of mobile inserts, a further distinction between standard and ultra-congruent inserts can also be made. Compared to the standard ones, ultra-congruent inserts are characterized by an increased anterior buildup, providing a more conforming articular surface that better matches the radius of the femoral component [19]. These inserts are able to guarantee a good anterior-posterior stability without the need of a metal cam [20,21], and with the even increased congruency, contact stress peaks are theoretically avoided, providing better stressforces distribution [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was post-cam mechanism polyethylene wear and a risk of dislocation [42,43], and the patella clunk syndrome might have occurred [44]. For many TKA brands, anterior-lipped ultracongruent (UC) J o u r n a l P r e -p r o o f inserts are available for when PCLs are damaged or resected, but increased constraint is provided by a "deep dish" polyethylene geometry instead of a post-cam mechanism [45][46][47][48][49]. Song et al reported no differences in mediolateral or anteroposterior laxity between UC TKA and CR TKA in stress radiographs at full extension, and concluded that UC inserts can be a good option in TKA without bony box cuts when the PCL is damaged during an operation [50].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Song et al reported no differences in mediolateral or anteroposterior laxity between UC TKA and CR TKA in stress radiographs at full extension, and concluded that UC inserts can be a good option in TKA without bony box cuts when the PCL is damaged during an operation [50]. Moreover, UC TKA is a safe alternative to PS TKA and similarly has good clinical outcomes if cruciate substitution is necessary in randomized control trials and propensity score-matched analyses [46,51,52]. Furthermore, the joint perception and isokinetic performance were similar between UC TKA and PS TKA [52,53].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%